Study of sRAGE, HMGB1, AGE, and S100A8/A9 Concentrations in Plasma and in Serum-Extracted Extracellular Vesicles of Pregnant Women With Preterm Premature Rupture of Membranes - Bouvier, Damien; Giguère, Yves; Blanchon, Loïc; Bujold, Emmanuel; Pereira, Bruno; Bernard, Nathalie; Gallot, Denis; Sapin, Vincent; Forest, Jean-Claude (Frontiers in Physiology, 2020)
Preterm premature rupture of membranes (PPROM), defined as rupture of fetal membranes prior to 37 weeks of gestation, complicates approximately 2–4% of pregnancies and is responsible for 40% of all spontaneous preterm births. PPROM arises from complex pathophysiological pathways with a key actor: inflammation. Sterile inflammation is a feature of senescence associated fetal membranes maturity. During specific steps of sterile inflammation, cells also release highly inflammatory damage-associated molecular pattern markers (DAMPs) such as High mobility group box 1 (HMGB1) or S100A8/A9, known to link and activate the receptor for advanced glycation endproducts (RAGE). The objective of this study was to measure longitudinally during pregnancy concentrations of sRAGE (soluble form of RAGE) and its main ligands (advanced glycation endproducts (AGE), HMGB1, S100A8/A9) in blood specimens. We studied 246 pregnant women (82 with PPROM and 164 matched control pregnant women without complications) from a cohort of 7866 pregnant women recruited in the first trimester and followed during pregnancy until delivery. sRAGE, AGE, HMGB1, S100A8/A9 concentrations were measured in plasma and in serum-extracted extracellular vesicles from 1st trimester (T1), 2nd trimester (T2), and delivery (D). In plasma, we observed, in both PPROM and control groups, (i) a significant increase of HMGB1 concentrations between T1 versus T2, T1 versus D, but not between T2 versus D; (ii) a significant decrease of sRAGE concentrations between T1 and T2, and a significant increase between T2 and D; (iii) a significant decrease of AGE from T1 to D; (iv) no significant variation of S100A8/A9 between trimesters. In inter-group comparisons (PPROM versus control group), there were no significant differences in time variation taking into account the matching effects. There was a correlation between plasma and serum-extracted extracellular vesicles concentrations of sRAGE, AGE, HMGB1 and S100A8/A9. Our results suggest that the rupture of fetal membranes (physiological or premature) is accompanied by a variation in plasma concentrations of sRAGE, HMGB1 and AGE. The study of RAGE and its main ligands in extracellular vesicles didn’t give additional insight into the pathophysiological process conducting to PPROM.